2013
DOI: 10.3892/ol.2013.1348
|View full text |Cite
|
Sign up to set email alerts
|

HER2 gene amplification in esophageal squamous cell carcinoma is less than in gastroesophageal junction and gastric adenocarcinoma

Abstract: The aim of the present study was to detect the amplification of the human epidermal growth factor receptor 2 (HER2) gene in esophageal squamous cell carcinoma (ESCC), gastroesophageal junction adenocarcinoma (GEJAC) and gastric cancer (GC), as well as to understand the pathological meaning of HER2 gene amplification with regard to clinico-pathological parameters in these types of cancer. HER2 gene amplification was evaluated by fluorescence in situ hybridization (FISH) in surgically obtained specimens from 76 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
3
13
1
Order By: Relevance
“…In contrast, HER2 positivity in a study developed by Gonzaga et al (18) was 21% in ESCC patients. In the current study, HER2/neu overexpression was observed in 4 patients (6%) (Score +3) of study population which is in line with some previously published reports (20,27). This variation may be due to the differences in IHC staining methods, different criteria for evaluating HER2 expression and different incidence of ESCC around the world.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In contrast, HER2 positivity in a study developed by Gonzaga et al (18) was 21% in ESCC patients. In the current study, HER2/neu overexpression was observed in 4 patients (6%) (Score +3) of study population which is in line with some previously published reports (20,27). This variation may be due to the differences in IHC staining methods, different criteria for evaluating HER2 expression and different incidence of ESCC around the world.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to the result of Yukie Sato et al study, no correlation was observed between tumor invasion and HER2/neu overexpression in present study (4). However, in JUN XING et al (20) study, HER2 gene amplification was correlated with the invasion of the ESCC cells. Therefore, further studies are required to provide more clarity regarding this issue.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Gastric carcinoma (GC) remains the second leading cause of cancer-related death worldwide (Huang et al, 2013). According to the statistics, the 5-year relative survival rate of gastric cancer patients is 24.3% (Shin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%